2013
DOI: 10.1002/pros.22642
|View full text |Cite
|
Sign up to set email alerts
|

A novel canine model for prostate cancer

Abstract: We have established a minimally invasive dog model of prostate cancer. This model may be valuable for studying prostate cancer progression and distant metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 25 publications
0
53
0
1
Order By: Relevance
“…56,96 Chemically immunosuppressed laboratory dogs have become established as orthotopic cancer models, particularly in prostate cancer research. 3,55 While the availability and cost often preclude the use of chemically immunosuppressed dogs in cancer research, their use as orthotopic models of bone metastasis can be valuable compared with rodents, particularly for translational in vivo imaging and treatment studies. Cats have a unique form of spontaneous bone metastasis in which pulmonary adenocarcinomas may metastasize to the bones of the digits.…”
Section: Animal Species Used For Bone Metastasis Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…56,96 Chemically immunosuppressed laboratory dogs have become established as orthotopic cancer models, particularly in prostate cancer research. 3,55 While the availability and cost often preclude the use of chemically immunosuppressed dogs in cancer research, their use as orthotopic models of bone metastasis can be valuable compared with rodents, particularly for translational in vivo imaging and treatment studies. Cats have a unique form of spontaneous bone metastasis in which pulmonary adenocarcinomas may metastasize to the bones of the digits.…”
Section: Animal Species Used For Bone Metastasis Researchmentioning
confidence: 99%
“…13). 55 The dogs develop prostate tumors that can be used for molecular imaging and focal therapy research. 116 Metastases have also occurred in lymph nodes and the lungs.…”
Section: Animal Modelsmentioning
confidence: 99%
“…For example, lique faction of tissue during histotripsy, in contrast to ther mal necrosis, can facilitate easier removal of destroyed tissue debris from the body. Recent preclinical histot ripsy trials on hyperplasia of the prostate gland (ade noma) in a dog model have shown that the destroyed tissue was removed through the excretory system over the course of several days [13]. To To develop HIFU protocols that utilize shock wave action on tissue, it is necessary to predict the charac teristic amplitude of shock fronts and the correspond ing peak pressures for a specific transducer or to develop transducers with specific parameters that ensure the desired shock wave field pressure levels.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it could be concluded that Cathepsin K has an important role in invasion and metastasis (Quintanilla-Dieck et al 2008). Progression of prostate tumour is facilitated in bone by Cathepsin K (Keller et al 2013). In case of colorectal carcinomas it is said that Cathepsin S plays novel roles in migration and invasion (Burden et al 2012).…”
Section: Cathepsinmentioning
confidence: 99%